Tinjauan Pendekatan Terbaru dalam Pengobatan Pneumonia Nosokomial dan Ventilator-Associated Pneumonia (VAP): Pendahuluan, Metode Penelitian, Hasil dan Pembahasan, Kesimpulan (Diikuti dengan Daftar Pustaka) - Prasanti, Amanda (Institut Teknologi dan Kesehatan Bintang Persada, 2026)
Nosocomial pneumonia, including ventilator-associated pneumonia (VAP), is one of the most common infections in hospitals and carries high morbidity and mortality rates. The increasing prevalence of multiresistant (MDR) pathogens has complicated the treatment of these infections and demands more innovative and evidence-based therapeutic approaches. This literature review aims to summarize the latest findings from ten recent studies related to treatment strategies for nosocomial pneumonia and VAP, particularly regarding the identification of MDR pathogens, the development of new therapeutic molecules, and the treatment approaches implemented. The review results indicate that prompt and appropriate empiric therapy, the use of biomarkers to guide therapy, and the application of newer-generation antibiotics play a crucial role in infection control. Furthermore, the implementation of prevention programs and microbiological surveillance are key to minimizing the spread of antimicrobial resistance. In conclusion, the treatment of nosocomial pneumonia and VAP must be carried out in an integrated, multidisciplinary approach that includes early detection, therapy tailored to local resistance patterns, and strengthening hospital prevention policies.